Coproantigen ELISA Effectively Detects Moderate-To-High Fasciola Egg Counts with Limited Sensitivity at Low Levels in Field Settings - Naim Che-Kamaruddin; Lokman Hakim Idris; Nur Mahiza Md Isa (Tropical Life Sciences Research, 2026)
Detection of Fasciola eggs in ruminant faecal samples typically occurs around 15 weeks post-infection during patent infections. The recent introduction of coproantigen ELISA (cELISA) enables rapid antemortem diagnosis of fasciolosis, highlighting the need to evaluate its diagnostic performance under the field conditions. This study aimed to assess the usability and effectiveness of a cELISA kit for detecting Fasciola gigantica infections in free-grazing cattle from an endemic area, and to explore the relationship between cELISA results and conventional faecal egg counts obtained via the Flukefinder® sedimentation method. A total of 92 faecal samples (46 positive and 46 negative by faecal egg count) were analysed. The cELISA detection limit was identified at 4.5 eggs per gram (epg), achieving 100% positivity above this threshold. A moderate, statistically significant positive correlation was observed between faecal egg counts and cELISA optical density (OD) values (Spearman’s r = 0.716, p < 0.01). Additionally, an odds ratio of 1.96 (p < 0.01) indicated that the likelihood of higher coproantigen levels nearly doubles with each additional egg detected. These findings suggest that cELISA is a sensitive and practical tool for diagnosing active Fasciola infections with moderate to high egg burdens, complementing traditional faecal sedimentation tests. Together, these approaches improve field diagnostics, enable targeted strategies and support effective fasciolosis control in endemic settings.